Implementasi Nilai-Nilai Pancasila Melalui Praktik Kebebasan Berpendapat di Indonesia - Saparina, Amalya Salsa; Dewi, Dinie Anggraeni (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2021)
This study aims to determine and understand that the implementation of Pancasila values ​​can be done with the practice of freedom of opinion. The research method carried out is a qualitative method. All information and facts are searched from various sources such as books, articles, journals, and so on. Freedom of opinion is one form of implementation of Pancasila. Freedoms can be done in the real world, and can also be done on social media (internet). This can implement Pancasila, if it does not violate government regulations, one of them is the ITE law. The study limitation is located in the process and research method. This article contributes to the reference enhancer that can help the community in conveying opinions. So, it can be concluded that freedom of opinion is one of the implementation of the Pancasila value in all precepts. With a note, the implementation is applied in the right way.